2008
DOI: 10.1002/j.0022-0337.2008.72.10.tb04597.x
|View full text |Cite
|
Sign up to set email alerts
|

Team‐Based Learning Using an Audience Response System: An Innovative Method of Teaching Diagnosis to Undergraduate Dental Students

Abstract: A team-based learning (TBL) approach was used to facilitate student learning and performance in a sophomore preclinical endodontic course. TBL is based upon the division of a class into small groups of students using a problem-based learning approach. The purpose of this project was to improve student ability to diagnose diseases utilizing TBL combined with an audience response system (ARS). Three measures were used to assess the outcomes: 1) pre-and posttest scores, 2) a diagnostic skills assessment during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 9 publications
(12 reference statements)
0
44
1
Order By: Relevance
“…Previous studies reported that TBL classes improved student diagnostic skills and student's critical analytic ability [8], National Board Examination results [10] and course grades on removable denture prosthesis [11]. According to our previous report [13], the average correct answer rate of TBL class showed higher term-end examination score than the regular class that teachers give the ordinary lectures.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies reported that TBL classes improved student diagnostic skills and student's critical analytic ability [8], National Board Examination results [10] and course grades on removable denture prosthesis [11]. According to our previous report [13], the average correct answer rate of TBL class showed higher term-end examination score than the regular class that teachers give the ordinary lectures.…”
Section: Discussionmentioning
confidence: 89%
“…Both class types (FC and TBL) are more likely to be effective than regular classes because our previous study showed that the average correct answer rate of TBL class showed higher term-end examination score than that of the regular class that teachers give the traditional lectures [13]. We consider that students can learn how to study by themselves in the active learnings (FC or TBL) [3,7,8,10,11,[13][14][15][16][17][18][19]and the difference between FC and TBL may not be big on the term-end examination score. We also have study limitation and we do not know the reason why there was no difference between FC and TBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nathaniel et al, 2016 in their meta-analysis found small but signi cant effects following the use of ARS technologies on both cognitive and non-cognitive learning outcomes [12]. However, few of the conducted trials studied ARS application for the undergraduate dental teaching programs, in particular in the eld of orthodontics [13,14]. The materials of the subject of orthodontics are considered to have a relatively high level of speciality and consequently are considered out of the scope of practice for a general dentist.…”
Section: Discussionmentioning
confidence: 99%
“…Team-based learning in nursing results in decreasing tension and study time and increasing preparation time for the class among nursing students, which make it possible to allocate more time for discussion about complicated nursing topics. 19 Other advantages of this method includes increasing class dynamics, 22 students involvement in class discussions, 18 increasing differential diagnosis skills in students and clinical experiences, decreasing the economic costs, 21 enhancing self-learning, 23 and stimulating higher levels of knowledge based on performance. 24 Moreover, team-based learning improves student performances in some healthcare educational courses.…”
Section: Introductionmentioning
confidence: 99%